The effect of bursectomy on the production of serum antibody againts ndvaccine in the indonesian native chickens and white leghorn - Hartini Sikar; D. Sastradipradja (Hemera Zoa, 1991)
Two groups of chickens were surgically bursectomized at 3 days of age. One week after the operation the experimental chickens were injected i.m. with ND vaccine starin La Sota. The 2nd injection was given 4 weeks after the ist injection. All injected chickens showewd an increase in HI-serum antibody titer. The response to the 2nd injection was higher than the ist The bursectomized animals showed lower HI antibody titer than the non busectomized after the ist injection, but a reverse response was observed after after the 2nd injection. Lymphocyte count showed a similar pattern as the HI antibody titer. Better responses were observed in the Indonesia native chicken compared to the white Leghorn. The increase of the serum globulin levels in both groups after the ist injection, the beta and gamma serum globulin levels in almost all injected chickens were elevated, except fot the bursectomized. White Leghorns, where the gamma globulin fraction was not increases.